Self Compassion Lanjut Usia di UPTD Pusat Pelayanan Sosial Griya Lansia Jawa Barat - Ramanda, Wulan Nur; Nurlela, Ella; Sinta Yulianti, Sinta Yulianti (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
This study examines the self compassion of the elderly in the UPTD of Griya Lansia Social Service Center West Java. This study aims to obtain an empirical picture of: 1) Respondent Characteristics, 2) Level of Self Kindness, 3) Level of Common Humanity, and 4) The level of Mindfulness owned by respondents. The method used in this research is a descriptive quantitative approach. The population of this study were 35 elderly people who were at the UPTD Social Service Center Griya Lansia West Java. Sampling in this study was carried out using saturated sampling technique. Data collection was carried out using a questionnaire consisting of 30 statements. Data collection was also carried out using observation techniques and documentation studies. The results showed that the level of self-kindness was in the high category with a total score of 1339 or 80%. The level of Common Humanity is in the medium category with a total score of 783 or 70%. The level of mindfulness is in the high category with a total score of 1155 or 83%. In general, the level of self-compassion of the elderly at the UPTD Griya Lansia Social Service Center is in the high category with a total score of 3277 or 78%. The problem analysis and needs analysis that has been carried out, the researcher proposes a program called “Improving the self-compassion of the elderly through social conversation groups at the UPTD Social Service Center of the West Java Home for the Elderly